Dynamic Precoder for Massive MIMO in the Presence of Large Doppler Spread - Shubhi, Ilmiawan; Murata, Hidekazu (2017 IEEE 85th Vehicular Technology Conference (VTC Spring), 2017)
Due to its ability to drastically improve the spectral efficiency, massive multiple-input multiple-output (MIMO) has become a strong candidate for the next wireless communication standard. Massive MIMO, however, relies its performance on the accuracy of the precoder. On the other hand, the drastic growth of traffic demand also requires the exploration of the underutilized frequency spectrum on the higher frequency bands. Unfortunately, transmission in these frequency bands will be largely affected by Doppler spread which reduces the accuracy of channel state information required by the precoder. To overcome this problem, a Doppler compensation technique for linear precoder in a massive MIMO scenario is proposed in this paper. By exploiting the channel reciprocity of time division duplexing transmission, we extract the Doppler shift information of the channel and use it to conduct the Doppler compensation by independently updating each element of the precoder matrix. Computer simulation shows that our proposed technique enables the massive MIMO transmission even when the value of maximum Doppler shift is considerably large.